Can Protanopia Be Correctly Diagnosed in Clinical Practice? An Evaluation of Diagnosis by Four Screening Tests. Issue 10 (October 2020) - Davison, Peter A.; Scanlon, Grainne
Abstract : SIGNIFICANCE: Protanopia is a color vision deficiency (CVD) that is unacceptable for certain occupations. This study compares simultaneously for the first time the ability of three recently revised or developed clinical tests of color vision with the Ishihara test to diagnose protanopia from other color vision deficiencies. PURPOSE: The objectives were to examine the ability of four clinical tests to differentiate (1) between protan and deutan CVDs in patients with protanopia and deuteranopia, and (2) protanopes and deuteranopes as "strong" deficiencies. METHODS: The Hardy-Rand-Rittler (4th ed.), City University (3rd ed.), Ishihara, and Mollon-Reffin tests were evaluated against the Oculus Heidelberg Multi-Color anomaloscope for 18 protanopes and 9 deuteranopes. Diagnosis by anomaloscopy was subsequent to administration of screening tests. RESULTS: The Ishihara test misdiagnosed all 18 protanopes as having a deutan deficiency. In contrast, the Hardy-Rand-Rittler and Mollon-Reffin tests correctly identified protan CVD in 100% of protanopes. No screening test was able to reliably diagnose protanopia on the basis of a strong protan CVD. CONCLUSIONS: The Ishihara test is not suitable for screening for protanopia; its failure to diagnose protanopes as having a protan CVD was far greater than that in previous studies. The Hardy-Rand-Rittler and Mollon-Reffin are the most reliable tests for this purpose. None of the screening tests were able to reliably differentiate dichromacy from strongly anomalous trichromacy. Abstract : Supplemental digital content is available in the text.